The Effect of Price to Book Value, Earning Per Share and Dividend Payout Ratio on a Company's Stock Price - Sindik Widati; Asep Tian Gunawan (Kusuma Negara Business School, 2021)
The movement of up and down stock prices in the capital market is interesting for investors, stock price movements can also be analyzed through various ratios. Therefore, investors need to know what ratios can be used to predict a company's stock. The purpose of this study is to determine the effect of Price to Book Value (PBV), Earning Per Share (EPS), and Dividend Payout Ratio (DPR) on Stock prices in automotive and component sub-sector manufacturing companies. The population of this research is the automotive and component sub-sector companies listed on the Indonesia Stock Exchange in 2017 – 2019 as many as 13 companies with a sampling technique that is purposive sampling and produces 9 companies to be tested. The analysis technique used is multiple linear regression analysis and hypothesis testing using t-statistics to test the partial regression coefficients and F-statistics to test the effect simultaneously with a 5% confidence level. In addition, all variables have been tested with the classical assumption test. The results showed that all variables passed the classical assumption test and were suitable to be used as research data. The results of the statistical t-test showed that the PBV variable partially had a significant negative effect on stock prices, the EPS variable partially did not affect stock prices and the DPR variable had a significant positive effect on stock prices. The results of the F test show that all variables simultaneously have a significant effect on stock prices.